Distribuição da concentração de mercúrio em sedimentos de praias adjacentes a foz do Rio Doce, Espírito Santo, Brasil - Cassa, Sonara Goncalves Silva (2021)
The disruption of the Fundão dam, in Mariana - Minas Gerais, occurred in November 2015, caused the spillage of a large amount of mining waste in the Rio Doce Basin. Mud spread along the river arriving its mouth in the northern of Espírito Santo. By the ac